Unlocking The Paradox (Effectiveness Of Public Relations In The E-Government Services Of The North Sumatra Ministry Of Region) - Khairiah, Nona; Zainun, Zainun; Indra, Farhan (UNIVERSITAS PAKUAN, 2024)
This research aims to investigate the implementation of e-Government in the Ministry of Religion of North Sumatra Province, with a focus on the challenges faced and strategies to increase its effectiveness. This research method uses a qualitative approach by conducting in-depth interviews with 20 respondents consisting of employees of the Ministry of Religion and people who use e-Government services. Data were analyzed using content analysis techniques to identify main patterns and themes from the interviews. The research results show that limited technological infrastructure, low public digital literacy, and concerns about data security are the main challenges in implementing e-Government. Recommended strategies include increased investment in technology infrastructure, digital literacy training, and improved data security policies to increase the acceptance and effectiveness of e-Government services in the future.